2020
DOI: 10.3390/molecules25092054
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Cobalt(II) Iodide with Pyridine and Redox Active 1,2-Bis(arylimino)acenaphthene: Synthesis, Structure, Electrochemical, and Single Ion Magnet Properties

Abstract: Complexes [(dpp-BIAN)0CoIII2]·MeCN (I) and [(Py)2CoI2] (II) were synthesized by the reaction between cobalt(II) iodide and 1,2-bis(2,6-diisopropylphenylimino)acenaphthene (dpp-BIAN) or pyridine (Py), respectively. The molecular structures of the complexes were determined by X-ray diffraction. The Co(II) ions in both compounds are in a distorted tetrahedral environment (CoN2I2). The electrochemical behavior of complex I was studied by cyclic voltammetry. Magnetochemical measurements revealed that when an extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 79 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…The loading capacity was then investigated with ICP mass spectrometry [ 46 , 47 ]. Products were synthesized with the addition of silver nitrate to MIL-101(Fe)@Ag of 0.0039 wt% (MIL-101(Fe)@Ag (Ag 0.0039 wt%)), 0.0101 wt% (MIL-101(Fe)@Ag (Ag 0.0101 wt%)), and 0.0127 wt% (MIL-101(Fe)@Ag (Ag 0.0127 wt%)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loading capacity was then investigated with ICP mass spectrometry [ 46 , 47 ]. Products were synthesized with the addition of silver nitrate to MIL-101(Fe)@Ag of 0.0039 wt% (MIL-101(Fe)@Ag (Ag 0.0039 wt%)), 0.0101 wt% (MIL-101(Fe)@Ag (Ag 0.0101 wt%)), and 0.0127 wt% (MIL-101(Fe)@Ag (Ag 0.0127 wt%)).…”
Section: Resultsmentioning
confidence: 99%
“…It is generally believed that bacterial growth is inhibited and bacteria are killed due to rupture of the bacterial cell membranes, thus leading to endoleaks, which results in the production of ROS and various free radicals [ 21 , 46 ]. ROS production has been found for various metal compounds, and these nanoparticles can lead to oxidative stress, inflammation, and consequent damage to proteins, cell membranes, and DNA, which is one of the main mechanisms of nanotoxicity [ 47 ]. The results of plate-coating experiments ( Figure 14 ) revealed that bacteria treated with MIL-101(Fe)@Ag (Ag 0.0127 wt%) produced more ROS than those treated with MIL-101(Fe), and few ROS were produced by bacteria not treated with MIL-101(Fe)@Ag (Ag 0.0127 wt%), indicating that the bacterial cell membranes treated with MIL-101(Fe)@Ag were disrupted and produced more ROS [ 32 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to large peak separations, except for the second cathodic reduction, cathodic (pc) and anodic (pa) peak potentials are otherwise given. Notably, 4-diethylamino-substituted BIAN L6 displayed an oxidation reaction that was fully reversible (E 1/2 = 0.67 V), which is extraordinary for this type of α-diimine ligand [38,44,[54][55][56].…”
Section: Electrochemical Characterizationmentioning
confidence: 97%
“…One of the most studied redox-active ligands are α-diimines or 1,4-diaza-1,3-butadienes [ 17 , 18 , 19 , 20 ]. Compounds of such ligands are mainly investigated for creating efficient catalysts [ 21 , 22 , 23 , 24 , 25 ], small molecules activation [ 26 , 27 , 28 ] and switchable materials [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. It has recently been found that platinum and palladium α-diimine complexes reveal cytotoxicity against various cancer cells [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%